DOMESTICATING AND MODERNIZING HEART OF DARKNESS - Kujawska-Lis, Ewa (Acta Neophilologica, 2013)
The present paper seeks to analyse the development of the translation series of Joseph Conrad’s Heart of Darkness with emphasis on domesticating and modernising tendencies. To this end, two translations into Polish are compared: Aniela Zagórska’s version published in 1930 and Ireneusz Socha’s modern translation of 2004. Various levels at which domesticating and modernising tendencies can be noticed are considered. It seems that, contrary to current tendencies to foreignize translated texts, the modern version of Heart of Darkness, at least at the linguistic level, may be labelled as the domesticated one in comparison with the earlier translation. Generally, Zagórska tries to reproduce Conrad’s wording in Polish; whereas Socha’s aim, or skopos, seems to be creating the text that reads naturally. The paper shows in what ways the translators’ choices of particular translating strategies and procedures accentuate the deforming tendencies, as defined by Antoine Berman.